2002
DOI: 10.1897/1551-5028(2002)021<0175:babeoc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Behavioral Effects of Carbofuran in Goldfish (Carassius Auratus)

Abstract: The effects of concentration (5, 50, and 500 microg/L) and duration (24, 48 h) of exposure to carbofuran, a carbamate insecticide, were assessed on brain catecholamine (norepinephrine [NE] and dopamine), plasma glucose, and hepatic glycogen contents and behavioral activities of goldfish (Carassius auratus). After 24 h of exposure to 50 and 500 microg/L, the level of NE was increased in the olfactory bulbs. The same effect was observed after a 48-h exposure to 500 and 50 microg/L in the telencephalic hemisphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The effect of carbofuran on brain catecholamines of goldfish was investigated. The exposure to 50 or 500 g/L carbofuran during 24 and 48 h caused a significant increase in catecholamines in distinct brain regions of goldfish (Bretaud et al, 2002). Our results have shown that ADP hydrolysis was significantly decreased after exposure to carbofuran, but there are no significant changes in ATP and AMP hydrolysis.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The effect of carbofuran on brain catecholamines of goldfish was investigated. The exposure to 50 or 500 g/L carbofuran during 24 and 48 h caused a significant increase in catecholamines in distinct brain regions of goldfish (Bretaud et al, 2002). Our results have shown that ADP hydrolysis was significantly decreased after exposure to carbofuran, but there are no significant changes in ATP and AMP hydrolysis.…”
Section: Discussionmentioning
confidence: 47%
“…However, several studies have showed that CB and OP compounds may affect second messenger systems, and consequently transduction signal pathways, which could exert a modulatory effect on ectonucleotidase activities. Therefore, in order to evaluate if ectonucleotidases may be modulated through an indirect effect of pesticides, we have performed in vivo experiments testing lower concentrations, in the concentration range that can be found in the environment (50 g/L) or can be considered a sublethal concentration for cyprinids (500 g/L) (Ansari and Kumar, 1984;Bretaud et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…14,77 The same effect was reported following a 48-hour exposure to carbofuran. 78 Subchronic exposure to malathion, enhanced hepatic gluconeogenesis and glycogenolysis, via stimulation of GP and phosphoenolpyruvate carboxykinase (PEPCK); whereas diazinon increased hepatic PEPCK. [79][80][81] Dichlorvos reduced the activity of hepatic GK and liver glycogen content while hepatic GK mRNA levels were increased.…”
Section: Pancreatic Injurymentioning
confidence: 99%
“…Exposed individuals may decrease activity (rainbow trout, Oncorhynchus mykiss, and aluminum; Allin and Wilson 1999, rainbow trout and copper;Campbell et al 2002), increase activity (e.g., stickleback, Gasterosteus aculeatus, and EE 2 ; Bell 2004), induce a change in circadian activity patterns (carp, Cyprinus carpio, exposed to PCBs and TBT; Schmidt et al 2005), or affect the location of activity (goldfish, Carassius auratus, and carbofuran; Bretaud et al 2002). Toxicants to which animals are exposed may have neurotoxic effects (e.g., methylmercury or many pesticides), producing cognitive or motor deficits that can reduce or increase movement (Brewer et al 2001;Bretaud et al 2002). High doses of contaminants can also increase the metabolic burden of the body (e.g., to repair toxicant damage), depleting energy reserves and reducing body condition (Campbell et al 2002).…”
Section: Introductionmentioning
confidence: 99%